Primary Incidence of Hepatitis C Virus Infection Among HIV-Infected Men Who Have Sex With Men in San Diego, 2000–2015. (3rd April 2019) - Chaillon, Antoine; Sun, Xiaoying; Cachay, Edward R; Looney, David; Wyles, David; Garfein, Richard S; Martin, Thomas C S; Jain, Sonia; Mehta, Sanjay R; Smith, Davey M; Little, Susan J; Martin, Natasha K
Abstract: Background: Little is known about the hepatitis C virus (HCV) epidemic among HIV-infected men who have sex with men (HIV+ MSM) in the United States. In this study, we aimed to determine the incidence of primary HCV infection among HIV+ MSM in San Diego, California. Methods: We performed a retrospective cohort analysis of HCV infection among HIV+ MSM attending 2 of the largest HIV clinics in San Diego. Incident HCV infection was assessed among HIV+ MSM with a negative anti-HCV test and subsequent HCV test between 2000 and 2017, with data censored to 2015. HCV reinfection was assessed among HIV+ MSM successfully treated for HCV between 2008 and 2015. Infection/reinfection rates were calculated using person-time methods. Results: Among 3068 initially HCV-seronegative HIV+ MSM, 178 new infections occurred over 15 796 person-years, giving an incidence of 1.13 per 100 person-years (/100py; 95% confidence interval [CI], 0.97–1.31). Incidence was stable from 2000 to 2014 (0.83/100py; 95% CI, 0.41–1.48), with an increase to 3.01/100py (95% CI, 1.97–4.42) in 2015 ( P = .02). Among 43 successfully treated patients, 3 were reinfected. Conclusions: HCV incidence is high among HIV+ MSM in San Diego, with evidence suggesting a recent increase in 2015. Strong HCV testing guidelines and active prevention efforts among HIV+ MSM are urgently needed that include rapid diagnosis, treatment, and risk reduction.